Social accountability and nursing education in South Africa - Susan J. Armstrong; Laetitia C. Rispel (Taylor & Francis Group, 2015)
Background: There is global emphasis on transforming health workforce education in support of universal health coverage. Objective: This paper uses a social accountability framework, specifically the World Health Organization's six building blocks for transformative education, to explore key informants' perspectives on nursing education in South Africa. Methods: Using a snowballing sampling technique, 44 key informants were selected purposively on the basis of their expertise or knowledge of the research area. Semi-structured interviews were conducted with the key informants after informed consent had been obtained. The interviews were analysed using template analysis. Results: South Africa has strategic plans on human resources for health and nursing education, training, and practice and has a well-established system of regulation and accreditation of nursing education through the South African Nursing Council (SANC). Key informants criticised the following: the lack of national staffing norms; sub-optimal governance by both the SANC and the Department of Health; outdated curricula that are unresponsive to population and health system needs; lack of preparedness of nurse educators; and the unsuitability of the majority of nursing students. These problems are exacerbated by a perceived lack of prioritisation of nursing, resource constraints in both the nursing education institutions and the health training facilities, and general implementation inertia. Conclusion: Social accountability, which is an essential component of transformative education, necessitates that attention be paid to the issues of governance, responsive curricula, educator preparedness, and appropriate student recruitment and selection.